Influence Of 12 Week Workouts On Physical Activity In Patients With Chronic Kidney Disease - Daminov Botir, Saipova Durdona, Egamberdieva Dano, Ruzmetova Iroda, Raimkulova Narina (International Journal of Advanced Science and Technology, 2020)
The article describes the definition of the physical activity of patients with chronic kidneydisease, as well as the effect of 12-week physical training on physical activity in patients with chronicdisease of stage 3-4 who are on a low-protein diet